New records of pyraloid moths (Lepidoptera: Pyraloidea) from different regions of Ukraine - Yepishin, Viktor; Khalaim, Yevhenii; Budashkin, Yuriy; Zhakov, Oleksandr; Mushynskyi, Vadym; Novytskyi, Sergiy (Zootaxa, 2021)
A list of 41 species of Crambidae and Pyralidae families recorded from different regions of Ukraine for the first time is given. Two species are found in Ukraine for the first time: Pyralis cardinalis Kaila, Huemer, Mutanen, Tyllinen & Wikström, 2020 and Euclasta splendidalis (Herrich-Schäffer, 1848), and two species are found in continental Ukraine for the first time: Diasemiopsis ramburialis (Duponchel, 1833) and Spoladea recurvalis (Fabricius, 1775). The hitherto unknown female genitalia of Bradyrrhoa imperialella (Ragonot, 1887) are described and the differences of external characters between females of B. imperialella and B. gilveolella (Treitschke, 1833) are briefly discussed. A brief note on the distribution of twin species Elegia atrifasciella Ragonot, 1887 and E. fallax (Staudinger, 1881) and Delplanqueia inscriptella (Duponchel, 1837) and D. dilutella ([Denis & Schiffermüller], 1775) in Ukraine is given.